Sex-specific associations of basal steroid hormones and neuropeptides with Conduct Disorder and neuroendocrine mediation of environmental risk - Bernhard, Anka; Kirchner, Marietta; Martinelli, Anne; Ackermann, Katharina; Kohls, Gregor; Gonzalez-Madruga, Karen; Wells, Amy; Fernández-Rivas, Aranzazu; De Artaza-Lavesa, Maider Gonzalez; Raschle, Nora Maria; Konsta, Angeliki; Siklósi, Réka; et al. (European neuropsychopharmacology, 2021)
Conduct Disorder (CD) is characterized by severe aggressive and antisocial behavior. The stress hormone system has frequently been investigated as a neurobiological correlate of CD, while other interacting neuroendocrine biomarkers of sex hormone or neuropeptide systems have rarely been studied, especially in females. We examined multiple basal neuroendocrine biomarkers in female and male adolescents with CD compared to healthy controls (HCs), and explored whether they mediate effects of environmental risk factors on CD. Within the FemNAT-CD study, salivary cortisol, alpha-amylase, testosterone, dehydroepiandrosterone-sulfate (DHEA-S), estradiol, progesterone, oxytocin, and arginine-vasopressin were measured under basal conditions in 166 pubertal adolescents with CD, and 194 sex-, age-, and puberty-matched HCs (60% females, 9-18 years). Further, environmental risk factors were assessed. Single hormone analyses showed higher DHEA-S, and lower estradiol and progesterone levels in both females and males with CD relative to HCs. When accounting for interactions between neuroendocrine systems, a male-specific sex hormone factor (testosterone/DHEA-S) predicted male CD, while estradiol and a stress-system factor (cortisol/alpha-amylase) interacting with oxytocin predicted female CD. Estradiol, progesterone, and oxytocin partly explained associations between early environmental risk and CD. Findings provide evidence for sex-specific associations between basal neuroendocrine measures and CD. Especially altered sex hormones (androgen increases in males, estrogen reductions in females) robustly related to CD, while basal stress-system measures did not. Early environmental risk factors for CD may act partly through their effects on the neuroendocrine system, especially in females. Limitations (e.g., basal neuroendocrine assessment, different sample sizes per sex, pubertal participants, exploratory mediation analyses) are discussed.
Gesehen am 25.10.2021